Intermolecular C−C Coupling between 1‐Methyl‐1, 2, 3‐Triazole and 2, 2′‐Bipyridine or 1, 10‐Phenanthroline in MoII Complexes. Issue 71 (20th October 2017) - Fombona, Sergio; Pérez, Julio; Díaz, Jesús; Riera, Lucía
Abstract: Unsupported 1‐methyl‐1, 2, 3‐triazole has been coordinated to {Mo(η 3 ‐methallyl)(CO)2 (N‐N)} (N‐N=2, 2′‐bipyridine, bipy; or 1, 10‐phenanthroline, phen) fragments, yielding cationic complexes that can be regarded as metalated triazolium salts. Their reactivity towards a strong base led to the deprotonation of the C5−H group of the triazole moiety, followed by an intermolecular nucleophilic attack to the ortho CH group of a bipy or phen ligand affording cyclic, bimetallic dearomatized C−C coupling products. The reaction of the neutral bipy derivative with an acid led to the formation of dihydropyridyl units by protonation of a CH group of the dearomatized rings, the dimeric nature of complexes being mantained upon protonation. Abstract : Talkin′ ′bout deprotonation : The deprotonation of the C5−H group of a 1‐methyl‐1, 2, 3‐triazole ligand leads to intermolecular nucleophilic attack of the ortho CH group of a bipy or phen ligand affording bimetallic dearomatized C−C coupling products (see figure).